Ministerial Decree No. 256/2015 Concerning Amending Certain Provisions of the Executive Regulation of the Customs Law Promulgated by Decree of the Minister of Finance No. 10 of the year 2006 = قرار وزاري رقم 256 لسنة 2015 بتعديل بعض أحكام اللائحة التنفيذية لقانون الجمارك بقرار وزير المالية رقم 10 لسنة 2006 / Minister Prime - Egypt. Minister Prime (2025)
Ministry of Finance Decree No. 256 of the year 2015 concerning amending certain provisions of the executive regulations of the customs law promulgated by decree of the minister of finance no. 10 of the year 2006 – وزارة المالية قرار رقم 256 لسنة 2015 بتعديل بعض أحكام اللائحة التنفيذية لقانون الجمارك الصادررة بقرار وزير المالية رقم 10 لسنة 2006